2009
DOI: 10.1371/journal.pgen.1000464
|View full text |Cite
|
Sign up to set email alerts
|

Epistatic Module Detection for Case-Control Studies: A Bayesian Model with a Gibbs Sampling Strategy

Abstract: The detection of epistatic interactive effects of multiple genetic variants on the susceptibility of human complex diseases is a great challenge in genome-wide association studies (GWAS). Although methods have been proposed to identify such interactions, the lack of an explicit definition of epistatic effects, together with computational difficulties, makes the development of new methods indispensable. In this paper, we introduce epistatic modules to describe epistatic interactive effects of multiple loci on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
117
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 57 publications
0
117
0
1
Order By: Relevance
“…Several epistatic effects have been identified in AMD datasets, mainly involving genegene interactions with complement factor H (CFH). [44][45][46][47][48] Furthermore, the effect of several variants has been found to be modified by smoking. 49,50 Combining genomic information with environmental factors or other types of omics data might improve the predictive accuracy to AMD susceptibility.…”
Section: Age-related Macular Degeneration (Amd)mentioning
confidence: 99%
“…Several epistatic effects have been identified in AMD datasets, mainly involving genegene interactions with complement factor H (CFH). [44][45][46][47][48] Furthermore, the effect of several variants has been found to be modified by smoking. 49,50 Combining genomic information with environmental factors or other types of omics data might improve the predictive accuracy to AMD susceptibility.…”
Section: Age-related Macular Degeneration (Amd)mentioning
confidence: 99%
“…In reference to SNP studies, risk models based on gene expression data have been conducted using relevant statistics (Tang et al, 2009), which will be explained in more detail in the following section. According to these models, samples are marked with a case-control label.…”
Section: Disease Occurrence Modelmentioning
confidence: 99%
“…In regards to risk model based on SNPs (Tang et al, 2009), the following risk models are used to model the phenotypic probability of genes as a cause of a disease. Different from SNP data, gene expression data are continuous rather than discrete.…”
Section: Disease Occurrence Modelmentioning
confidence: 99%
“…We observed that the marginal effect of CFH is predominant in both two-842 interactions with SGCD and MED27. While SGCD has been reported to be associated with AMD [14], the relationship between MED27 and AMD has been uncovered.…”
Section: Case Study Ill: Age-related Macular Degeneration (Amd) Datasetmentioning
confidence: 99%